Investigating the toxicological effects of nanomaterials in food packaging associated with human health and the environment - Gupta, Rakesh Kumar; Guha, Proshanta; Srivastav, Prem Prakash (Journal of hazardous materials letters, 2024)
Nanomaterials (NMs) have revolutionized food packaging by offering unique properties such as enhanced barrier functions, antimicrobial activity, and prolonged shelf life. However, concerns over the potential adverse effects of these materials on human health and the environment have prompted extensive research. This review explores the toxicological implications of NMs used in food packaging, focusing on their migration mechanisms, interactions with biological systems, and environmental impact. NMs, due to their small size and high surface area-to-volume ratio, can migrate from packaging materials into food under various conditions, potentially leading to human exposure through ingestion. Studies have highlighted the ability of certain NMs, such as silver nanoparticles (AgNPs), titanium dioxide nanoparticles (TiO2 NPs), and zinc oxide nanoparticles (ZnO NPs), to induce oxidative stress, inflammation, genotoxicity, and cellular dysfunction in vitro and in vivo. Furthermore, the environmental release of NMs during manufacturing, use, and disposal stages poses risks to ecosystems and human health. This review synthesizes current knowledge, identifies research gaps, and discusses regulatory challenges associated with the safe use of NMs in food packaging. Future research directions are proposed to enhance the understanding of NM toxicity, improve risk assessment methodologies, and develop sustainable packaging alternatives. By addressing these issues, stakeholders can effectively manage the risks while harnessing the benefits of nanotechnology in food packaging innovation. [Display omitted] •Increasing use of nanomaterials (NMs) in food packaging raises concerns about potential exposure to consumers and environment.•Health risks include respiratory, inflammatory responses and cellular toxicity depending on the type and dose of NMS.•Studies suggest that nanoparticles can migrate from packaging into food under high temperature and acidity condition•Release of NMs into the environment can affect soil and water ecosystems, potentially disrupting microbial communities.•Limited regulatory frameworks exist for assessing the safety of NMs in food packaging.